A Modified Approach for Isolation of Vibrio vulnificus from Aquaculture Settings - Thandapani, Muthulakshmi; Sivam, Visnuvinayagam; Geethalakshmi, V.; Swaminathan, T. R.; Prasad, M. M. (Fishery Technology, 2025)
The isolation of Vibrio vulnificus is crucial forunderstanding its prevalence and pathogenicity. The isolation procedure to enhance the detection of V. vulnificus in aquaculture samples was optimized using a double plate differentiation method. The plates used were Thiosulphate Citrate Bile Salt Sucrose Agar (TCBS) and Hichrome Agar Vibrio. Two independent studies were conducted: one involving the addition of fish samples with physiological saline as diluent, and the other with Alkaline Peptone Water (APW) enrichment. Our findings revealed that direct plating without enrichment, prior to the selection of presumptive colonies on TCBS agar, significantly increased the likelihood of isolating V. vulnificus. The molecular identity of this pathogen was confirmed using PCR targeting the vvh gene. Additionally, significant variations in the abundance of V. vulnificus were observed in different aquatic samples, emphasizing the importance of sample type in isolation efficiency. The enrichment procedure yielded a 2.9% prevalence, whereas the direct plating resulted in a 10.2% prevalence of the bacteria. Furthermore, this study underscores the necessity of direct plating to optimize the isolation process of V. vulnificus from diverse aquatic sources. The developed procedure for isolation of V. vulnificus is less time-consuming, less expensive (